2021
DOI: 10.33902/jpr.2021067651
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and mapping of the literature of virtual reality studies in earth science engineering education

Abstract: Today, earth sciences engineering education programs face with serious problems. It is often not possible to provide experience on different geographical environments or materials. Considering these problems of earth science related engineering education programs, virtual reality environment potentially can provide technology enhanced training alternatives. However, in the literature there are not many studies showing how virtual reality can enhance the earth science related engineering education programs. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In recent years, virtual reality has received signi cant attention as a next generation's platform even though this is not a recent new technology. Along with the increasing interest on virtual reality, cases using it as well as research studies are rapidly expanding [1][2][3][4][5][6][7][8][9][10][11]. Technical developments such as head-mounted display (HMD), controllers, and motion tracking systems as well as content development that apply virtual reality to games, movies, advertisements, exhibitions in museums, and education are rapidly growing in various areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, virtual reality has received signi cant attention as a next generation's platform even though this is not a recent new technology. Along with the increasing interest on virtual reality, cases using it as well as research studies are rapidly expanding [1][2][3][4][5][6][7][8][9][10][11]. Technical developments such as head-mounted display (HMD), controllers, and motion tracking systems as well as content development that apply virtual reality to games, movies, advertisements, exhibitions in museums, and education are rapidly growing in various areas.…”
Section: Introductionmentioning
confidence: 99%
“…ese studies reviewed the previous articles to answer specific research questions for understanding important keywords or topics of the field. Some review papers focused on the trends of virtual reality-based education research related to specific fields as shown in Table 1, such as Earth science engineering education [7], medical education [8,19], STEM education [20], math education [21], computer science education [22], higher education [23][24][25], heritage education [26], rehabilitation management of breast cancer survivors [27], virtual reality-based training for daily living in patients with chronic stroke [28], PSTD treatments [29], foreign language learning gamification using virtual reality [30,31], K-12 and higher education [15,17], surgical training [32], industrial skills training [31], virtual reality cognitive training in individuals with mild cognitive impairment [16,18], science education [33,34], sensorimotor learning [35], dental education [36], virtual reality-based emotional response and symptom provocation in patients with OCD (obsessive compulsive disorder) [37], nursing education [38,39], virtual reality therapy for social anxiety disorder [40], evacuation training [41], virtual reality-assisted neuromuscular therapy [42], home-based virtual reality rehabilitation for individuals with Parkinson disease [43], virtual realitybased physiology and anatomy learning [44], social work education [45], and marketing higher education …”
Section: Introductionmentioning
confidence: 99%